(untitled) (Jurnal Pembangunan Sosial, 2009)
This study was conducted to identify factors influencing loyalty towards organization among exempt and non-exempt employees in the government sector. Factors examined are management support, career development, job security, training and development, and compensation. Data collected through self-administered questionnaires, whereby 356 sets were distributed and 349 sets (98.03%) were analyzed. Pearson Correlation and Multiple Regression analyses were used to analyze the data. Findings indicate that all factors examined have positive correlation with the loyalty among employees. Regression analysis showed that management support, job security, and training and development have influenced on the level of loyalty among employees towards organization. Therefore, it is crucial for the top management to take into account these factors in improving loyalty among employees.